2022
DOI: 10.1038/s41598-022-21435-6
|View full text |Cite
|
Sign up to set email alerts
|

Quinoline–imidazole/benzimidazole derivatives as dual-/multi-targeting hybrids inhibitors with anticancer and antimicrobial activity

Abstract: Two new classes of hybrid quinoline–imidazole/benzimidazole derivatives (the hybrid QIBS salts and QIBC cycloadducts) were designed and synthesized to evaluate their anticancer and antimicrobial activity. The strategy adopted for synthesis is straight and efficient, in four steps: N-acylation, N-alkylation, quaternization and a Huisgen 3 + 2 cycloaddition. The in vitro single-dose anticancer assay of forty six hybrid quinoline-benzimidazole compounds reveal that one QIBS salt (11h), has an excellent quasi nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 42 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…In continuation of our concern for new compounds with antimicrobial activity, Diaconu et al [ 52 ] synthesized a large library of hybrid imidazole- and benzimidazole-quinoline derivatives and studied their antimicrobial properties. The reaction pathway ( Scheme 42 ) involves an initial N -acylation reaction of 8-aminoquinoline, followed by an N -alkylation of the -NH- amino group from imidazole/benzimidazole heterocycle, when the key imidazole-quinoline 128a , b and benzimidazole-quinoline 129a , b hybrids are obtained.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our concern for new compounds with antimicrobial activity, Diaconu et al [ 52 ] synthesized a large library of hybrid imidazole- and benzimidazole-quinoline derivatives and studied their antimicrobial properties. The reaction pathway ( Scheme 42 ) involves an initial N -acylation reaction of 8-aminoquinoline, followed by an N -alkylation of the -NH- amino group from imidazole/benzimidazole heterocycle, when the key imidazole-quinoline 128a , b and benzimidazole-quinoline 129a , b hybrids are obtained.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37] The quinoline core has also proven anti-cancer and anti-microbial activities. 38,39 Several studies have reported anti-cancer activities against diverse cell lines when functionalising this versatile heterocycle with hydrazide substitution. [40][41][42] Introduction of a nitro group at the 8th position on the quinoline ring stabilises the moiety through hydrogen bonding with the ring nitrogen atom.…”
Section: Introductionmentioning
confidence: 99%
“…53 Further, the amide functional group is also an option to increase the antimicrobial activity, as understood from the literature. 55,56 Thus, an amidate-based aminoquinoline group linked with alkyl chains can exhibit enhanced antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, many of the reported pharmaceutical compounds contain nitrogen-based heterocycles, for example, the quinoline pharmacophore. More specifically, functionalized quinoline can play a very important role in increasing the therapeutic propensity of the drugs. Quinoline drugs can induce apoptosis, inhibit the cell cycle, and disrupt cell migration to damage pathogenic cells, and most importantly, they are promising against biofilm-associated infections. , Moreover, the introduction of electron-releasing alkyl chains and biologically active morpholine into the copper complexes can enhance antimicrobial activity. The SAR studies show that compounds having methyl substitution at one end and electron-withdrawing groups at the other side can increase the electrophilic nature of the compound and thus facilitate the nucleophilic attack over the cellular thiol groups . Further, the amide functional group is also an option to increase the antimicrobial activity, as understood from the literature. , Thus, an amidate-based aminoquinoline group linked with alkyl chains can exhibit enhanced antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%